The modelling and analysis of hand arm vibration in order to reduce industrial vibration exposure - Najafi Amin, Amir (Curtin University, 2017)
This research investigates the vibration transmissibility from the vibrating handle to the handarm of the operator, and it suggests a practical way to measure vibration at different locations of the hand simultaneously. Furthermore, it investigates the vibration behaviour of different commercial damping materials experimentally and generates analytical models for them. Then it combines these models with the lumped-mass model of the hand-arm system for simulating the performance of the glove which uses the damping material.